EFEKTIVITAS KONSEP STIFIN DALAM MENGATASI KESULITAN BELAJAR SANTRI DI PONDOK PESANTREN DARUL FAROH KOTA BATAM - Sulistiyo, Galuh; Muji; Salfiah; Neli Artika Yanti; Mia Erika Febriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the STIFIn concept in addressing learning barriers experienced by students at the Darul Faroh Islamic Boarding School in Batam City. The primary focus of this study is sleepiness, boredom, and low focus during the learning process. This study used a descriptive qualitative approach with 31 students mapped based on the Intelligence Engine (4 Sensing, 5 Thinking, 8 Intuiting, 9 Feeling, and 5 Instinct). Data were collected through participant observation and in-depth interviews to explore the effectiveness of this genetic-based intervention. The results showed that implementing learning strategies aligned with the students' intelligence types significantly minimized learning barriers. The Feeling and Intuiting groups, as the dominant groups, showed increased enthusiasm after receiving emotional appreciation and the use of visual media. This study concludes that the STIFIn concept is an effective tool for educators at Islamic boarding schools in identifying and addressing psychological barriers to learning in a personalized and targeted manner.